Investitionsbereitschaft und zeitliche Indifferenz bei Realinvestitionen unter Unsicherheit und Steuern - Caren Sureth; Armin Voß (Arbeitskreis Quantitative Steuerlehre (arqus), 2005)
We analyze the impact of taxation on the option to defer an investment decision and derive tax rates that do not influence the extent of postponement. Furthermore, we deduce from this option pricing framework a measure of an investor's disposition towards realizing an investment project under risk aversion. We show that capital gains taxation often reduces this disposition, whereas asymmetric tax treatment of profits and losses may compensate this effect at least partially. On this basis, we identify indifferent curves that describe different tax schedules providing constant disposition to invest. These curves enable a comparison of different tax rules and their impact on investment decisions without explicitly referring to the after-tax value of an investment project. Thereby, the decisionmaking process is simplified. Applying individual utility functions we finally analyze the influence of taxation on the investor's – decision and on utility-based decisions. We highlight the overwhelming importance of integrating taxes in typically applied valuation approaches.
Keywords: H25; H21; 330; asymmetric taxation; capital gains tax; investment decisions; risk aversion; uncertainty; Wertzuwachssteuer; Veräußerungsgewinn; Steuerwirkung; Betriebliche Investitionspolitik; Risikoaversion; Theorie